Neonatal morbidity service of Maria Auxiliadora Hospital, Lima - Castillo, María (2015)
We report the morbidity and mortality of a group of 1229 RN treated at a six-month period (October 86-April 87) and coming from the south of Lima, marginal urban area. 65% were normal RN that did not require more care than routine, 35% requirireron different care, because they had some kind of pathology. The RN 1229, were PEG 139 (11.3%), AEG 995 (81%) and 95 GEG (7.7%). AEG sick 32.2%, the 55.4% PEG sick and ill GEG 40%. Mortality is 1% for AEG, 1.1% for the GEG and 6.5% for the PEG. The risk of disease and death was greater for men. Below 1.500 g., 95% sick and low mortality is 71.4%. 3.1% were premature, 1% were underweight. Premature babies are at increased risk of illness and death, sick and die 75.6% to 30%. The most frequent morbidity was intrauterine hypoxia, 20%, followed by infections, 15.4% (sepsis, 6.9%). The neonatal mortality rate was 16 per 1,000 including neonatal sepsis (30%) meconium aspiration (20%) syndrome.